Enzymatic and microenvironmental regulation in adenosine metabolism-mediated immunosuppression - Li, Chuang; Chen, Lifeng; Li, Zhihao; Liang, Ling; Lou, Benyong (Frontiers in Immunology, 2026)
Adenosine (ADO), as an endogenous purine nucleoside, can regulate almost all aspects of tissue function. However, its abnormal accumulation in the tumor microenvironment (TME) induces immune tolerance and promotes tumor immune evasion by activating adenosine receptors (ADOR). Regulating ADO metabolism in the TME holds promise for ameliorating ADO-mediated immunosuppression and restoring antitumor immune responses. Extensive research has highlighted the pivotal role of ADO in tumor immune suppression and preclinical development of inhibitors targeting ADOR. However, systematic integration in ADO metabolism of microenvironmental influences, enzyme and protein regulation, and targeted intervention strategies through multiple pathways remain insufficient. This review systematically summarizes the key aspects of targeting ADO-mediated immunosuppression, including the feature of TME, enzymes involved in ADO metabolism (e.g., CD39/CD73/ADK/ADA), and ADOR interventions. Additionally, the necessity of comprehensively regulating ADO metabolism and the immune microenvironment through multi-level coordinated interventions is also explored, as well as the latest combined regulatory strategies. Moreover, the major challenges in current research on ADO metabolic regulation are also critically analyzed and the future research directions are proposed to address the dual challenges of ADO metabolic diversity and TME complexity, aiming to develop more precise and effective immunotherapeutic strategies.